(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Objective: To identify independent risk factors, assess the clinical role of the occurrence of wound dehiscence after PSARP in pediatric patients with anorectal malformations and to determine the frequency. Material and Method: The study was conducted as a prospective cohort study in a tertiary surgical center specializing in children’s surgery from January 2023 to December 2025. The children enrolled were those who were ≤12 years old at PSARP or staged PSARP. Wound dehiscence was partial or complete separation of the midline perineal wound, necessitating clinical intervention. A p-value of <0.05 was considered statistically significant. Results: 218 patients were enrolled and 31 (14.2%) had wound dehiscence. High/intermediate malformation type (p=0.003), complications in relation to the colostomy (p=0.011), operation of more than 3 hours (p=0.008) and the weight-for-age that was below the 5th percentile (p=0.024) showed significant univariate associations. The surgeon’s experience level (p=0.14) and the type of prophylactic antibiotic (p=0.29) did not appear to be associated. Conclusions: The incidence of wound dehiscence in children undergoing PSARP is 1/7, and is correlated with the complexity of the surgery, length of surgery and nutritional status at surgery. Such perioperative optimization that employs a protocol (including nutritional rehabilitation) can minimize this complication. Anorectal malformations (ARMs) are a common complication of posterior sagittal anorectoplasty (PSARP) surgery, with a 0.6% incidence of surgical site complications.